PENGARUH CORPORATE GOVERNANCE, DAN MODEL BISNIS TERHADAP PENGHINDARAN PAJAK - Karel Michael Martin; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the relationship between Corporate Governance, and Business Models on Tax Avoidance in manufacturing companies in Indonesia. Corporate Governance is divided into seven sections Executive Compensation, Executive Character, Firm Size, Institutional Ownership, Board of Commisioner, Audit Commitee, and Audit Quality.The population in this study are all companies listed on the Indonesia Stock Exchange for 2016 - 2018. The sampling method used in this study is purposive sampling. The number of samples used in this study were 113 research samples. The data used in this study were obtained from the company's annual report. The data in this study were analyzed using multiple regression techniques. Data in this study were also analyzed using the classic assumption test before being analyzed using multiple regression techniques. The results of this study indicate that Executive Character, Institutional Ownership, Board of Commisioner, Audit Commitee, and Audit Quality and Business Models do not conflict with Tax Avoidance, while Executive Compensation an Firm Size affect Tax Avoidance.